2019
DOI: 10.3390/ma12233998
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Functional Properties of a Novel Apatite-Ionomer Cement for Prevention and Remineralization of Dental Caries

Abstract: Especially in pediatric dentistry, prevention by the control of initial lesions prior to cavitation is very important, and application of a pit and fissure sealant is essential to achieve this. Numerous reports have suggested that resin-based sealants are inferior to sealants based on glass-ionomer cement (GIC), because of GIC’s many advantages, such as fluoride ion release properties and its good adhesion to tooth structures. However, the use of GIC is impeded due to its low flexural strength and fracture tou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 34 publications
0
16
0
1
Order By: Relevance
“…Hydroxyapatite and hydroxyapatite-based composites are widely used in dentistry and orthopedics [27][28][29]. They have also confirmed good performances in infection scenarios [30,31].…”
Section: Introductionmentioning
confidence: 83%
“…Hydroxyapatite and hydroxyapatite-based composites are widely used in dentistry and orthopedics [27][28][29]. They have also confirmed good performances in infection scenarios [30,31].…”
Section: Introductionmentioning
confidence: 83%
“…The improvement of the mechanical properties of GIC based materials is of significant clinical importance since GIC materials are more biocompatible than dental resins, but their mechanical properties are relatively weaker [1,3,6]. Moreover, it was previously reported that HA incorporated into GIC improved the strength of GICs, but it also increased the release of fluoride ions contributing to anticariogenic properties of these materials, which is clinically truly relevant [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…CS was even lower than with modification with 3% ( w / w ) TiO 2 NP. It was previously suggested that the HAp particles dispersed in FAS react with polyalkenoic acid similarly to HAp from dentin and enamel: the ionic attraction between carboxyl groups from GIC and the calcium ions in the HAp of enamel and dentine results in the displacement of calcium and phosphate ions from the HAp and the formation of an ion-exchange layer of calcium and aluminium phosphates and polyacrylates at the interface [ 2 , 29 , 30 , 31 ]. These additional matrix layers should improve mechanical properties.…”
Section: Discussionmentioning
confidence: 99%